Health system innovations in Central America : lessons and impact of new approaches - La Forgia, Gerard M. (Gerard Martin) (World Bank working paper, 2005)
Similar to developing countries elsewhere, during the 1990s, Central American countries faced pressures to improve the performance of their health systems. In most countries, there was a consensus that the systems were failing to live up to their potential. Rather than take on system-wide change, each country opted to step into reform through launching innovations to address specific problems or deficiencies in a particular program, function or intervention of the system. Health Systems Innovations in Central America reports on how these experiences fared -- a hospital in Panama, a nutrition p.